Total synthesis and target identification of marine cyclopiane diterpenes - Tian Li; Shan Jiang; Yuanhao Dai; Xia Wu; Huihui Guo; Liang Shi; Xueli Sang; Li Ren; Jie Wang; Lili Shi; Wenming Zhou; Houhua Li; et al. (Nature Communications)
Abstract Marine cyclopianes are a family of diterpenoid with novel carbon skeleton and diverse biological activities. Herein, we report our synthetic and chemical proteomics studies of cyclopiane diterpenes which culminate in the asymmetric total synthesis of conidiogenones C, K and 12β-hydroxy conidiogenone C, and identification of Immunity-related GTPase family M protein 1 (IRGM1) as a cellular target. Our asymmetric synthesis commences from Wieland-Miescher ketone and features a sequential intramolecular Pauson-Khand reaction and gold-catalyzed Nazarov cyclization to rapidly construct the 6-5-5-5 tetracyclic skeleton. The stereocontrolled cyclopentenone construction is further investigated on complex settings to demonstrate its synthetic utility. Furthermore, using an alkyne-tagged conidiogenone C-derived probe, IRGM1, a master regulator of type I interferon responses, is identified as a key cellular target of conidiogenone C responsible for its anti-inflammatory activity. Preliminary mechanism of action studies shows that conidiogenone C activates IRGM1-mediate dysfunctional mitochondria autophagy to maintain mitochondria quality control of inflammatory macrophages.